2001
DOI: 10.1017/s0266467401001043
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dung presence, dung amount and secondary dispersal by dung beetles on the fate of Micropholis guyanensis (Sapotaceae) seeds in Central Amazonia

Abstract: ABSTRACT. The study of seed fate is crucial for understanding fruit-frugivore interactions. One factor that can greatly influence the fate of seeds dispersed through mammal defecation, is the dung that accompanies the seeds. Dung attracts dung beetles and rodents; the former eat and bury dung, the latter feed on seeds. In this study the fate of Micropholis guyanensis subsp. guyanensis seeds surrounded by no dung and by 5, 10 and 25 g of howler monkey dung was followed until seedling establishment. The depths a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
3
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(103 citation statements)
references
References 46 publications
6
91
3
3
Order By: Relevance
“…In line with this, some studies asserted, dung beetles play a role on burying seeds and their activity should be taken into consideration (Andresen 2001;Andresen and Levey 2004). The second result of this study showed that seed dispersal affected by different functional groups.…”
Section: Discussionsupporting
confidence: 75%
“…In line with this, some studies asserted, dung beetles play a role on burying seeds and their activity should be taken into consideration (Andresen 2001;Andresen and Levey 2004). The second result of this study showed that seed dispersal affected by different functional groups.…”
Section: Discussionsupporting
confidence: 75%
“…Scatter-hoarding rodents generally reduce seed-clumping, as they remove individual seeds from tapir latrines (Fragoso 1997), bat feeding roosts and other sites of concentrated seed deposition and then most often cache seeds individually (Forget & Milleron 1991). Dung beetles also generally move one or a few seeds at a time from the clumps found in defecations of primates and other mammals, and thus spread those originally concentrated seeds over a greater area through their activities (Andresen 2001). On the other hand, central-place foragers such as ants may increase clumping of seed deposition by collecting seeds from a wide area and depositing most of them within the relatively smaller area of the nest or its refuse piles (Passos & Oliveira 2002).…”
Section: Patternsmentioning
confidence: 99%
“…Hypothetically at least, the disappearance of many euglossine bees in the BDFFP fragments could reduce the fecundity of orchids, which rely entirely on euglossines for pollination (Powell and Powell 1987). Likewise, the decline in fragments of dung beetles, which bury dung for their larvae that often contains seeds, might reduce seed survival and germination for some plant species (Klein 1989, Andresen 2001.…”
Section: Changes In Ecological Processesmentioning
confidence: 99%